Hyperinfection by Strongyloides in captive callitrichids with progressive weight loss syndrome. Issue 4 (9th June 2021) - Conga, David F.; de Souza, Natalia F.; Jaques, Adriana M. C. C.; Benigno, Raimundo N. M.; Pereira, Washington L. A.
Abstract: We report three cases of disseminated hyperinfection by Strongyloides in primates Callithrix jacchus and Callithrix penicillata in captivity and with progressive weight loss syndrome. Histopathological examination revealed severe lesions in lungs, liver, and intestines with the presence of Strongyloides larvae and in a generalized manner, including other organs such as the pancreas and heart.